European Green Deal Objective for Sustainable Agriculture: Opportunities and Challenges to Reduce Pesticide Use - Muska, Aina; Pilvere, Irina; Nipers, Aleksejs (Emerging Science Journal, 2025)
Agriculture in the 21st century faces complex global challenges, including rising food demand, resource depletion, and climate change. These pressures, however, also create opportunities to foster sustainability, enhance resource efficiency, and reduce reliance on synthetic pesticides. In response, the European Union (EU) adopted the European Green Deal in 2019, aiming for climate neutrality by 2050. The Farm to Fork (F2F) strategy sets a specific target: reducing chemical pesticide usage and its related risks by half by 2030. This study aims to assess the overall situation in the EU and the Member States' contributions to achieving the F2F objective of reducing pesticide use as well as risks at the policy level. A novel methodological approach was developed to assess Member State performance using a set of EU-defined indicators – such as Harmonised Risk Indicators (HRI 1 and HRI 2), pesticide sales data from Eurostat and FAOSTAT – and to classify countries into contribution-based groups. Findings reveal progress at the EU level: pesticide sales have declined and HRI 1 has dropped, but HRI 2 has increased. Significant variation among Member States was observed, highlighting the need for tailored policy actions. The study provides an innovative framework and practical insights for policymakers and stakeholders working toward sustainable agricultural transitions in the EU.